Indiscriminate friendliness in foster children: Associations with attachment security, foster parents' sensitivity, and child inhibitory control. (June 2020) - Schoemaker, Nikita K.; Vermeer, Harriet J.; Juffer, Femmie; Spies, Ruan; van Ee, Elisa; Maras, Athanasios; Alink, Lenneke R. A.
Indiscriminate friendliness (IF) is atypical behavior often seen in postinstitutionalized and foster children. The current exploratory study examined the associations of children's attachment security, parental sensitivity, and child inhibitory control with reported and observed IF in 60 family-reared, never-institutionalized foster children. IF was measured with a parent-report questionnaire (Indiscriminate Friendliness Questionnaire) and an observational measure (adapted version of the Stranger at the Door procedure; Bucharest Early Intervention Project). Attachment security and inhibitory control were related to reported IF (i.e., a secure attachment and poor inhibitory control were associated with higher levels of IF), but parental sensitivity was not. No associations were found between observed IF and attachment security, parental sensitivity, or inhibitory control. Thus, foster children with a secure attachment relationship may be more prone to socially interact with others including strangers, whereas better inhibitory control may serve as a buffer against IF but these results were found for reported IF only. More research is needed to gain more knowledge about different measures, other possible correlates, and underlying mechanisms of IF.